Does Boris‐SDC conserve phase space volume?. Issue 1 (21st October 2015) - Winkel, Mathias; Speck, Robert; Ruprecht, Daniel
Abstract: In this paper we investigate the conservation of phase space volume of the Boris‐SDC algorithm. This method provides a generic way to extend the standard, second‐order accurate Lorentz force integrator commonly used for charged particles in an electric and magnetic field to a high‐order method using spectral deferred corrections. For a single particle in a Penning trap and different frequencies of the electric and magnetic fields, we assess the conservation properties of the method by computing the update matrix of one step of Boris‐SDC as well as its determinant. We compare the results to the convergence regions and relate them to energy conservation properties of the method. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)